Histoenzymic Distribution Pattern In Gall Bladder Of Sheep (Applied Biological Research, 2018)
The present study was conducted on gall bladder of < 1 year-old sheep  (n = 9) to elucidate the distribution of enzymes viz., alcoholic dehydro genase, glucose-6-phosphate dehydrogenase, glutamic dehydrogenase,  lactic dehydrogenase, malic dehydrogenase, reduced nicotinamide  adenine dinucleotide diaphorase, reduced nicotinamide adenine  dinucleotide phosphate-diaphorase and succinic dehydrogenase. The  histoenzymic distribution of monoamine oxidase, non-specific esterase,  alkaline phosphatase and glucose-6-phosphatase was also recorded.  The study revealed moderate to intense activity in glandular areas of  gall bladder for majority of enzymes reflecting higher metabolic  activity. The enzyme activity was weak to moderate in different tunics  of gall bladder and mild to moderate in vascular areas. The differential  enzyme activity in different tunics of gall bladder was correlated with  metabolic activity of cells.
Keywords: Enzyme; gall bladder; histochemistry; postnatal; sheep